Functional Immunity and Mens Rea: Rethinking Criminal Liability of Notaries as Public Officials - Sri Ratu Ratna Intan; Agus Surono; Agung Iriantoro; Tetti Samosir; Ibrahim Abyan Loftus (Universitas Negeri Semarang, 2026)
The criminal prosecution of notaries for acts performed within their statutory duties raises a fundamental question regarding the proper boundary of criminal liability for public officials. In criminal law, liability is grounded in the principle of culpability, commonly expressed as nullum delictum, nulla culpa (no punishment without fault), which requires subjective fault as a prerequisite for punishment. This principle has long been emphasized by criminal law scholars such as Jan Remmelink and Moeljatno, who argue that criminal liability can arise only when fault is present and no exculpatory grounds exist. In the Indonesian context, this principle has been explicitly codified in Law No. 1 of 2023 on the Criminal Code, particularly under Articles 22 and 36–44, which emphasize fault-based criminal liability and the relevance of personal circumstances in determining culpability. Despite this normative clarity, the application of criminal law to notaries often raises doctrinal tension, especially when formal notarial acts are linked to unlawful outcomes without clear proof of intention, knowledge, or negligence. This article examines the criminal liability of notaries as public officials through the lens of mens rea and functional immunity to reassess the legitimacy of penal intervention against notarial acts. Employing a doctrinal and comparative legal approach, this research analyzes criminal liability theory alongside legal frameworks in Indonesia, the Netherlands, and France. The study finds that criminal liability must be strictly grounded in subjective fault, and that notarial acts performed within statutory authority require careful differentiation between formal duties and personal misconduct. The article argues that, rather than assuming the absence of liability, the assessment of notarial responsibility must be based on a structured evaluation of mens rea, while recognizing the need for proportional legal protection for acts performed within official capacity. This approach aims to prevent overcriminalization while maintaining accountability, thereby aligning the enforcement of criminal law with the fundamental principle of culpability.